Problematisasi Batas Usia Anak 18 Tahun dalam Hukum Indonesia: Antara Kepastian Hukum dan Dinamika Kasus Aktual - Intan Nur’Aini; Anggita Lailatun Ni’mah; Aurellia Mirabel Fredlyna (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The establishment of the age limit for children up to 18 years in Indonesian law is a normative instrument that aims to ensure legal certainty and child protection. This provision is adopted in various laws and regulations as a form of the state's commitment to fulfilling children's rights. However, in law enforcement practice, the application of this age limit often causes problems when faced with the dynamics of actual cases that reveal a discrepancy between the normative age and the social, psychological, and factual conditions of the child. This condition creates tension between the legal-formal approach that emphasizes legal certainty and the need for substantive justice oriented towards the best interests of the child. This study aims to analyze the problems of applying the age limit of 18 years in the context of actual cases and to examine how the tension between legal certainty and the reality of children is reflected in law enforcement practices in Indonesia. The research method used is normative legal research with a legislative and conceptual approach, as well as normative qualitative analysis. The results of the study show that the rigid application of the age limit for children has the potential to ignore the contextual aspects of children and give rise to inconsistencies in practice. Therefore, a more contextual legal approach is needed through strengthening the discretion of law enforcement officials and progressive interpretation by judges in order to achieve substantive justice and optimal protection for children.